Comparison of the shaping ability of Mtwo and S5 NiTi rotary files in simulated canals - Demet Altunbaş; Alper Kuştarcı; Kerem Engin Akpınar; Dilara Arslan (Gazi University, 2016)
OBJECTIVE: The aim of this study was to compare the shaping ability of Mtwo and S5 nickel-titanium rotary instruments during the preparation of simulated curved canals. MATERIALS and METHOD: Forty simulated canals were randomly assigned to two groups (n=20). Canals were prepared to apical size 30 by using Mtwo or S5 files. Preoperative and postoperative images of the canals were obtained by using a digital camera, images were superimposed and aberrations were recorded. Material removal was measured at 5 different points. Statistical analysis was performed using Kolmogorov-Smirnov test, independent t-test and chi-square test at a significance level of 0.05. RESULTS: The mean total width of the canals in the Mtwo group was significantly greater than the S5 group except the apical end-point of the preparation (p<0.05). Mean absolute transportation was less than 0.20 mm at all measurement points. However there were significant differences between the systems for the magnitude of the transportation at three points: halfway from the beginning of the curve to the orifice, beginning of the curve, and apex of the curve (p<0.05). S5 created significantly less transportation at the beginning of the curve and at the apex of the curve, but created significantly greater transportation at halfway from the beginning of the curve to the orifice (p<0.05). No perforation, ledge, zip, or elbow was created during instrumentation. One S5 instrument fractured, and two S5 and five Mtwo instruments deformed. A mean loss of working length of 0.21 mm for Mtwo and 0.22 mm for S5 was measured, with no statistically significant difference found between the groups (p>0.05). CONCLUSION: Mtwo produced wider canal shape. S5 provided more centered apical preparation and maintained the original canal shape well.